Attribution analysis of the Ethiopian drought of 2015 - Philip, S; Kew, S; van Oldenborgh, GJ; Otto, F; O'Keefe, S; Haustein, K; King, A; Zegeye, A; Eshetu, Z; Hailemariam, Z; Singh, R; Jjemba, E; et al. (American Meteorological Society, 2018)
In northern and central Ethiopia, 2015 was a very dry year. Rainfall was only one-half to three-quarters of the usual amount, with both the Belg (Feb–May) and Kiremt rains (Jun–Sep) affected. The timing of the rains that did fall was also erratic. Many crops failed, causing food shortages for many millions of people. We investigated the role of climate change in the probability of drought like this, focusing on the large-scale precipitation deficit in February–September 2015 in northern and central Ethiopia. Using a gridded analysis that combines station data with satellite observations, we estimate that the return period of this drought was more than 60 years (lower bound 95% C.I.), with a most likely value of several hundred years. We cannot detect a trend in the observations, but the large natural variability and short time series means large trends could go undetected in the observations. Two out of three large climate model ensembles that simulated rainfall reasonably well show no trend while the third shows an increased probability of drought. Taking the model spread into account we again cannot attribute the drought to anthropogenic climate change, with the 95% confidence interval ranging from a probability decrease between pre-industrial and now of a factor 0.3 and an increase of a factor 5 in a drought like this one or worse. A soil moisture data set also shows a non-significant drying trend. According to ENSO correlations in the observations, the strong 2015 El Niño did increase the severity of the drought.